2010
DOI: 10.3346/jkms.2010.25.9.1375
|View full text |Cite
|
Sign up to set email alerts
|

Severe Hypertriglyceridemia in Diabetic Ketoacidosis Accompanied by Acute Pancreatitis: Case Report

Abstract: We report a case of diabetic ketoacidosis (DKA) and hypertriglyceridemia (severely elevated to 15,240 mg/dL) complicated by acute pancreatitis, which was treated successfully with insulin therapy and conservative management. A 20-yr-old woman with a history of type 1 diabetes came to the emergency department 7 months after discontinuing insulin therapy. DKA, severe hypertriglyceridemia and acute pancreatitis were diagnosed, with DKA suspected of contributing to the development of the other conditions. In Korea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
64
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(72 citation statements)
references
References 15 publications
3
64
0
2
Order By: Relevance
“…A literature search revealed that hypertriglyceridemia associated with hyponatremia and DKA has been described in at least one other case report. In that previous report, the etiology of this significant degree of hyponatremia was unknown and the hyponatremia corrected with the administration of IV 3% NaCl solution 20. In our patient, close observation and a change in the sodium concentration in the IVF’s (1/2NS to NS) resulted in resolution of the perceived hyponatremia.…”
Section: Discussionsupporting
confidence: 46%
“…A literature search revealed that hypertriglyceridemia associated with hyponatremia and DKA has been described in at least one other case report. In that previous report, the etiology of this significant degree of hyponatremia was unknown and the hyponatremia corrected with the administration of IV 3% NaCl solution 20. In our patient, close observation and a change in the sodium concentration in the IVF’s (1/2NS to NS) resulted in resolution of the perceived hyponatremia.…”
Section: Discussionsupporting
confidence: 46%
“…32 Once dyslipidemia is diagnosed in children with type 1 diabetes, the dyslipidemia should be treated per lipid guidelines for adults with diabetes. 22 Blood pressure was elevated in our two patients.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that 24.7-79.0% of patients with DKA have non-specific elevation of amylase or lipase. For this reason, DKA is reported to mask a co-existing AP in 10-15% of cases [11]. Timely diagnosis of AP in DKA is critical as it would change the course of treatment.…”
Section: Discussionmentioning
confidence: 99%